The Application of the Quantum Teaching Method to Improve the Learning Outcomes of Aqidah Akhlak of Class VII Students of Madrasah Tsanawiyah Manbaul Uluum Musi Banyuasin - Rindi Apriliyani; Khoirul Anwar (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to determine the effectiveness of the Quantum Teaching method in improving the learning outcomes of seventh-grade students in Akidah Akhlak at Madrasah Tsanawiyah Manbaul Uluum, Musi Banyuasin Regency. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 24 students, and data were collected through observation, interviews, documentation, and tests, then analyzed using descriptive qualitative and quantitative approaches. The results showed that before the implementation of Quantum Teaching, students’ learning outcomes were low, with only 25% achieving the minimum mastery criteria. After applying the method, there was a significant improvement, with most students achieving scores above the minimum standard. Additionally, this method increased students’ activeness, motivation, and enthusiasm in the learning process. Therefore, it can be concluded that the Quantum Teaching method is effective in improving students’ learning outcomes in Akidah Akhlak.